THE INFLUENCE OF BUDGET PARTICIPATION , BUDGET PRESSURE , AND ASYMMETRICAL INFORMATION ON BUDGET ASYMMETRY AT PT. PP. LONDON SUMATRA INDONESIA,Tbk. - Kristiawan, Ganda (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to examine the influence of Budget Participation, Budget Pressure, and asymmetrical information on Budget Asymmetry. The population was 72 business units at PT. PP. London Sumatra. The research subjects were 167 respondents, consisted on Managers, Heads of Administration Department, and Deputy Heads of PT. PP.  London Sumatra Indonesia, Tbk. The data were analyzed by using multiple linear regression analysis with an SPSS (Statistical Package for Social Science) version 22.0 software program. The result of the research showed that Budget Participation and Budget Pressure had positive and significant influence on budget asymmetry, while asymmetrical information had negative and significant influence. Simultaneously, the three variables had significant influence on budget asymmetry.